Effects of CO2 Enrichment on Growth and Development of Impatiens hawkeri. (9th November 2011) - Zhang, Fan-Fan; Wang, Yan-Li; Huang, Zhi-Zhe; Zhu, Xiao-Chen; Zhang, Feng-Jiao; Chen, Fa-Di; Fang, Wei-Min; Teng, Nian-Jun
Abstract : The effects of CO2 enrichment on growth and development of Impatiens hawkeri, an important greenhouse flower, were investigated for the purpose of providing scientific basis for CO2 enrichment to this species in greenhouse. The plants were grown in CO2 -controlled growth chambers with 380 (the control) and 760 (CO2 enrichment) μ mol·mol −1, respectively. The changes in morphology, physiology, biochemistry, and leaf ultrastructure of Impatiens were examined. Results showed that CO2 enrichment increased flower number and relative leaf area compared with the control. In addition, CO2 enrichment significantly enhanced photosynthetic rate, contents of soluble sugars and starch, activities of peroxidase (POD), superoxide dismutase (SOD), and ascorbate peroxidase (APX), but reduced chlorophyll content and malondialdehyde (MDA) content. Furthermore, significant changes in chloroplast ultrastructure were observed at CO2 enrichment: an increased number of starch grains with an expanded size, and an increased ratio of stroma thylakoid to grana thylakoid. These results suggest that CO2 enrichment had positive effects on Impatiens, that is, it can improve the visual value, promote growth and development, and enhance antioxidant capacity.